ІНСТИТУЦІЙНЕ ЗАБЕЗПЕЧЕННЯ УПРАВЛІННЯ РИЗИКАМИ БІЗНЕСУ В УМОВАХ ЦИФРОВІЗАЦІЇ - Kyfyak, Viktoria (ПРОБЛЕМИ ІННОВАЦІЙНО- ІНВЕСТИЦІЙНОГО РОЗВИТКУ, 2022)
Анотація. Флуктуації, що змінюють середовище розвитку бізнесу, такі як пандемія та воєнні дії, зумовлюють необхідність зміни парадигми управління бізнесом, у якій ризик-менеджмент і цифровізація є основою конкурентних бізнес-моделей, що й робить тему актуальною в нинішніх складних реаліях функціонування бізнесу. Метою статті є обґрунтування інституційного забезпечення управління ризиками та цифрових інструментів як необхідних компонент бізнес-моделей у сучасних умовах. Методологія дослідження. У статті використано методи системного підходу та структуризації як базису виявлення основних проблем і тенденцій розвитку механізму управління ризиками в умовах цифровізації. Застосовано також такі загальнонаукові методи, як аналіз, синтез і діалектика. Новизна. Визначено динаміку зміни парадигм управління ризиками в системі управління підприємствами. Охарактеризовано інституції управління ризиками в умовах цифровізації та вказано ризики, які загрожують у цих умовах. Висновки. Обґрунтовано, що багаторівневість і багатоаспектність природи ризику потребують дослідження структури ризиків та механізму їх впливу на діяльність підприємства крізь призму інституційного середовища, яке визначає особливості та специфікацію трансформації фактору на джерело ризику в конкретний період часу й на визначеній території.
INSTITUTIONAL SUPPORT OF BUSINESS RISK MANAGEMENT IN THE DIGITAL CONDITIONS
Summary. Fluctuations that change the business environment, such as pandemics and hostilities, necessitate a change in the paradigm of business management, in which risk management and digitalization are the basis of competitive business models, which makes the topic relevant in today’s complex business realities. The aim of the article is to substantiate the institutional support of risk management and digital tools as a necessary component of business models in modern conditions. Research methodology. The article uses methods of systematic approach and structuring as a basis for identifying the main problems and trends in the development of risk management mechanism in the context of digitalization. And also used such general scientific methods as analysis, synthesis and dialectics. Novelty. The article identifies the dynamics of changes in risk management paradigms in the enterprise management system. It is substantiated that multilevel and multifaceted nature of risk requires study of the structure of risks and the mechanism of their impact on the enterprise through the prism of the institutional environment, which determines the features and specification of the transformation of the factor into a source of risk in a given period and territory. It is proposed to apply the coefficient of digitalization of business processes, which will determine the degree of dependence of the business process on digital threats. It is proposed to determine the institutional support for risk discrimination, through the results of institutions aimed at monitoring and identifying external business risks and those based on operational data on fluctuations in the economic system. Conclusions. The institutions of risk management in the conditions of digitalization are defined and characterized and the risks that threaten in these conditions are identified. Key global trends in corporate security have been studied. The digital tools such as cognitive computing, ERP and MES systems and SAS-style software for risk management and for building an effective business model in the face of new social challenges are described. Thus, institutional support for risk description (international organizations and standards aimed at improving the risk management mechanism) in combination with modern digital tools in business can form a competitive, progressive business model that can integrate risks into development opportunities.
Keywords: Ключові слова: ризик, управління ризиками, цифровізація, інсти- туційне середовище, інституції, цифрові інструменти управління ризиками.